Removal of transient disturbances from oscillating measurements using nearest neighbors imputation. (August 2016) - Cecílio, Inês M.; Ottewill, James R.; Fretheim, Harald; Thornhill, Nina F.
Abstract : Highlights: Method to remove transient disturbances from oscillating measurements. Reconstructed measurement maintains the original oscillatory dynamic features. Method is based on a nearest neighbors imputation technique. Optimal parameter values adaptable to dynamics of any particular system. Inconsistency indices to assess the adequacy of the reconstructed measurement. Abstract: Transient disturbances in process measurements compromise the accuracy of some methods for plant-wide oscillation analysis. This paper presents a method to remove such transients while maintaining the dynamic features of the original measurement. The method is based on a nearest neighbors imputation technique. It replaces the removed transient with an estimate which is based on the time series of the whole measurement. The method is demonstrated on experimental and industrial case studies. The results demonstrate the efficacy of the method and recommended parameters. Furthermore, inconsistency indices are proposed which facilitate the automation of the method.